ENHANCING STUDENTS' SPEAKING SKILL BY USING THINK PAIR SHARE COLLABORATED WITH VIDEO AT SMPN 2 LUBUKLINGGAU - Dwi Maulianto Dwi (CV Grasta Glory, 2025)
This study aims to determine the completeness of learning outcomes of the effectiveness the Think Pair Share (TPS) strategy combined with video in improving students’ speaking skills at SMPN 2 Lubuklinggau. A pre-experimental method was applied using one group pre-test and post-test design, involving 38 eighth-grade students. The sampling technique used was random sampling technique. The prerequisite analysis technique uses normality test while the hypothesis used a sample t-test. The pre-test showed an average score of 58.57 with a standard deviation of 10.47, where only 29% of students reached the